Chemical composition and antinutritional factors of Lycianthes synanthera leaves (chomte) - Salazar Meléndez de Ariza, Elsa Julieta (2006)
Abstract The leaves of Lycianthes synanthera (chomte), an edible Guatemalan plant, were analysed for some nutritional and antinutri tional factors. Results of this study indicated that chomte leaves are rich sources of Ca, K, Fe, Zn, Cu, ascorbic acid, riboflavin, crude protein, carbohydrates and energy. Chomte leaves had hemagglutinating activity, trypsin inhibiting activity of 43.2 ± 1.0 TIU mg protein 1 and a-amylase inhibiting activity of 3.2 ± 0.9 AIU mg protein 1 . A cooking treatment, 15 min boiling, resulted in a considerable decrease in antinutritional factors. 2005 Elsevier Ltd. All rights reserved